Beauty Is In the Eye of the Credit Card Holder? Antecedents of Credit Card Usage and Credit Card Debt - Tan, Shu Han (2017)
Credit cards have become a common form of payment over the past fifty years, replacing both cash and the cheque that were once commonly used as payment mechanism. However, in recent years, the rising level of credit card debt is concerning. This study addresses this public issue by investigating the antecedents of credit card usage and the level of credit card indebtedness. The author collected data from credit card holders (aged 18-65) by using mixed method approach. Focus group interviews and short survey questionnaire were employed to acquire data from participants. The results show that credit card characteristics such as its low payment transparency and utility functions are factors that influence consumers’ credit card usage. Furthermore, age of credit card users also found to be associated with the usage of credit card. Meanwhile, regarding credit card debt, the results indicate that individual’s age, value, and attitudes are determinants that affect consumers’ likeliness to incur credit card debt. Consumers’ materialism and their spending behaviours cannot be fully linked to credit card debt, but the findings on this current study offer useful understanding on this issue. Lastly, the author draws on the findings to provide public policy implications.